Implementing Literacy Culture and Digital Literacy in the Early Grades of Primary School - APRILIA, ELSA FIRDA (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Literacy culture and digital literacy are crucial in shaping students’ early learning experiences. This study aims to describe literacy culture and digital literacy activities in the early grades while identifying the supporting and inhibiting factors in their implementation. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, with data validity ensured through triangulation. The research was conducted at SD Muhammadiyah 1 Jember, East Java. The findings reveal that literacy culture is fostered through activities such as establishing reading corners, reading books before lessons begin, and providing a school library. Digital literacy is integrated through the use of an E-Library and various digital learning tools employed by teachers. Several supporting factors contribute to the success of these initiatives, including the school’s role in providing infrastructure and the students’ interest in reading. However, challenges remain, such as incomplete infrastructure, lack of parental support, and an unsupportive environment. These findings highlight the importance of institutional support and community involvement in enhancing literacy culture and digital literacy from an early age. Strengthening these aspects can significantly contribute to students’ cognitive and social development in an increasingly digital era.